2007
DOI: 10.1562/0031-8655(2003)0780331omomea2.0.co2
|View full text |Cite
|
Sign up to set email alerts
|

Objective Measurement of Minimal Erythema and Melanogenic Doses Using Natural and Solar-simulated Light¶

Abstract: Very little information exists on the amount of natural and artificial UV light required to cause sunburn and tanning in individuals with very pale skin who are at the greatest risk of developing skin cancer. We have investigated minimal erythema dose (MED) and minimal melanogenic dose (MMD) in a group of 31 volunteers with Fitzpatrick skin types I and II using an Oriel 1000 W xenon arc solar simulator and natural sunlight in Sydney, Australia. We measured the erythemal and melanogenic responses using conventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…Our results are in keeping with past studies that have found that skin reflectance measurements of pigmentation correlate with ssUV MED in normal individuals (13,16,17) and narrowband-UVB MED (311 nm TL-01) in psoriatic patients (10). Broadband UVB MED studies have shown conflicting results, with some showing a correlation (12,14,22), while others have not (6,7).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our results are in keeping with past studies that have found that skin reflectance measurements of pigmentation correlate with ssUV MED in normal individuals (13,16,17) and narrowband-UVB MED (311 nm TL-01) in psoriatic patients (10). Broadband UVB MED studies have shown conflicting results, with some showing a correlation (12,14,22), while others have not (6,7).…”
Section: Discussionsupporting
confidence: 88%
“…The erythema index (EI) was calculated by comparing the amount of reflected light at 546 nm, which is inversely proportional to the amount of haemoglobin or blood content in the superficial dermis, with a reference signal at 632 nm to compensate for skin tone. Dose responses for erythema have been previously quantified with an erythema meter (7,(16)(17)(18) or chromameter (6, 18) using linear regression.…”
Section: Determination Of Skin Erythemamentioning
confidence: 99%
See 1 more Smart Citation
“…The L à and b à values have been used extensively to study changes in melaninderived color. [11][12][13] Our results showed a decrease in yellow color corresponding to a lightening of hyperpigmented areas (b à value) and an increase in skin brightness (L à value), with a significant improvement as early as after the first treatment. The increase in brightness was recorded throughout the study, although at Week 6 it failed to reach significance (p = 0.0654).…”
Section: Discussionmentioning
confidence: 79%
“…While several studies reported the use of colorimetry [4,9] and spectrophotometry [10] to assess SPT, Pershing et al used spectrophotometry to objectively determine all six SPTs using only constitutive skin color independent of UVL-induced erythema [2] . The "gold standard" method of assessing skin pigmentation is spectrophotometry; however, it is difficult to perform spectrophotometry under clinical conditions.…”
Section: Introductionmentioning
confidence: 99%